The role of the mesolimbic dopamine system in the formation of blood-oxygen-level dependent responses in the medial prefrontal/anterior cingulate cortex during high-frequency stimulation of the rat perforant pathway. Issue 12 (December 2016) - Helbing, Cornelia; Brocka, Marta; Scherf, Thomas; Lippert, Michael T; Angenstein, Frank
Several human functional magnetic resonance imaging studies point to an activation of the mesolimbic dopamine system during reward, addiction and learning. We previously found activation of the mesolimbic system in response to continuous but not to discontinuous perforant pathway stimulation in an experimental model that we now used to investigate the role of dopamine release for the formation of functional magnetic resonance imaging responses. The two stimulation protocols elicited blood-oxygen-level dependent responses in the medial prefrontal/anterior cingulate cortex and nucleus accumbens. Inhibition of dopamine D1/5 receptors abolished the formation of functional magnetic resonance imaging responses in the medial prefrontal/anterior cingulate cortex during continuous but not during discontinuous pulse stimulations, i.e. only when the mesolimbic system was activated. Direct electrical or optogenetic stimulation of the ventral tegmental area caused strong dopamine release but only electrical stimulation triggered significant blood-oxygen level-dependent responses in the medial prefrontal/anterior cingulate cortex and nucleus accumbens. These functional magnetic resonance imaging responses were not affected by the D1/5 receptor antagonist SCH23390 but reduced by the N-methyl-D-aspartate receptor antagonist MK801. Therefore, glutamatergic ventral tegmental area neurons are already sufficient to trigger blood-oxygen-level dependent responses in the medial prefrontal/anterior cingulate cortex and nucleus accumbens. Although dopamine release alone does not affect blood-oxygen-level dependent responses it can act as a switch, permitting the formation of blood-oxygen-level dependent responses.